2020
DOI: 10.1088/1755-1315/584/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing protein, lipid and carbohydrate levels in diets for growth of juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ x E. lanceolatus ♂)

Abstract: Hybrid grouper (Epinephelus fuscoguttatus ♀ χ E. lanceolatus ♂) that is well known as “cantang” has a good prospect for aquaculture due to its high economic value, fast growing and good acceptance to compound feed. However, information on feed specification for this grouper is still limited. Therefore, this research aimed to find out the good proportions of protein, lipid and carbohydrate in feed for hybrid grouper. Six experimental diets were formulated with protein contents of 48, 44 and 40%, which then comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The previous study reported that 7% dietary lipid at 45~55% dietary protein levels improved the grouper growth performance as it increased PER, but higher dietary lipid (10%, 13%) significantly reduced PER and appeared higher intraperitoneal fat ratio, and the results indicated ingestion of excess lipid induced a lipid deposition [22]. However, other studies demonstrated that 14% dietary lipid at 50% dietary protein level [33] or 16% dietary lipid at 44% dietary protein level [21] could keep higher PER and subsequently The data of the table is expressed by mean average value ± standard error (n = 3). The significant difference is exhibited in the same column with different superscript letters (P < 0:05).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The previous study reported that 7% dietary lipid at 45~55% dietary protein levels improved the grouper growth performance as it increased PER, but higher dietary lipid (10%, 13%) significantly reduced PER and appeared higher intraperitoneal fat ratio, and the results indicated ingestion of excess lipid induced a lipid deposition [22]. However, other studies demonstrated that 14% dietary lipid at 50% dietary protein level [33] or 16% dietary lipid at 44% dietary protein level [21] could keep higher PER and subsequently The data of the table is expressed by mean average value ± standard error (n = 3). The significant difference is exhibited in the same column with different superscript letters (P < 0:05).…”
Section: Discussionmentioning
confidence: 94%
“…Currently, numerous researches of hybrid grouper on the nutrition was mainly reported on requirement of dietary protein and lipid level, protein to energy ratio, amino acid patterns, requirement of arginine and isoleucine, addition amount of corn starch, etc. [21][22][23][24][25][26]. Moreover, there are also many studies reporting that the substitution by nonfish meal protein sources (soy protein, soybean meal, peanut meal, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that 7% dietary lipid at 45%–55% dietary protein levels increased PER and thus improved grouper growth performance, but higher dietary lipids (10% and 13%) significantly reduced PER and elevated intra-abdominal lipid ratios, leading to lipid deposition in various tissues of the fish [ 5 ]. Another study showed that 50% protein and 14% lipid [ 30 ] or 44% protein and 16% lipid [ 6 ] can promote the growth of hybrid groupers. Therefore, HLD (42% protein and 16% lipid) was used in this study to maintain higher PER and WGR.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of dietary lipids (10%, 13%) decrease PER while increasing abdominal lipid deposition [ 5 ]. Other studies showed that higher levels of dietary lipids (16%) were significantly accelerated the growth rate of grouper while significantly increasing the crude lipid content of the fish in all tissues, suggesting that high-lipid diets lead to excessive lipid deposition in all tissues of grouper [ 6 ]. A high-lipid diet (HLD) with a lipid level of 16% and protein level of 42% was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment diets ( Table 1 ) were designed to have same crude protein (CP, 464.7 g/kg), crude lipid (CL, 70 g/kg), and gross energy (340 kcal/100 g dry matter), referring to previous studies [ 26 28 , 30 , 31 ]. The overall dietary amino acid contents ( Table 2 ) were adjusted accordingly based on our researches on the reference amino acid profile [ 24 ] and the optimum dietary requirements for leucine [ 25 ], methionine [ 27 ], arginine [ 28 ], and threonine [ 30 ].…”
Section: Methodsmentioning
confidence: 99%